Pediatric Central Nervous System Tumors in Nigeria: A systematic Review of Treatment and Long-Term Patient Outcomes - Santillana Linares, Luciana (2025)
Analysis of data from 1960 to 2017 revealed an incidence rate of 226.98 cases of central nervous system (CNS) tumors per 100,000 population in Africa, with Nigeria having a significantly higher number of cases than other African countries1. CNS tumors are the fourth most common type of pediatric tumor in Nigeria2, leading to a growing interest in the state of pediatric neuro-oncologic care in Nigeria. This study aims to provide an epidemiological overview of the presentation, diagnoses, treatment modalities, and outcomes of pediatric patients with CNS tumors in Nigeria from 1962 to 2023.